Stigma, Identity, and CriticalityThe Impetus, Function, and Expression of Disclosure - Joshua C. Collins; Tonette S. Rocco (Adult Education Research Conference, 2015)
This paper explores the impetus, function, and expression of disclosure (revealing of guarded personal information) and articulates some key insights regarding what critical adult learning and education can gain from understanding disclosure as a phenomenon, particularly for people with invisible stigmatized identities.